PREVALENCE OF THALASSEMIA IN THE VIETNAMESE POPULATION AND BUILDING A CLINICAL DECISION SUPPORT SYSTEM FOR PRENATAL SCREENING FOR THALASSEMIA - Danh Cuong Tran; Anh Linh Dang; Thi Ngoc Lan Hoang; Chi Thanh Nguyen; Thi Ngoc Mai Dinh; Van Anh Tran; Thi Kim Phuong Doan; Thi Trang Nguyen (Mediterranean Journal of Hematology and Infectious Diseases, 2023)
Background and objectives. Investigating the prevalence of thalassemia in the Vietnamese population, building a clinical decision support system for prenatal screening for thalassemia.